Climate finances: regional and local aspects of use - Борисюк, Олена Володимирівна; Карлін, Микола Іванович; Стащук, Олена Володимирівна; Дацюк-Томчук, Марія Богданівна; Ліповська-Маковецька, Наталія Іванівна; Borysiuk, Olena V.; Karlin, Mykola I.; Stashchuk, Olena V.; Datsiuk-Tomchuk, Mariia B.; Lipovska-Makovetska, Nataliіa I. (Perspectives of modem scientific research, 2018)
The global warming that we are facing now induces international organizations to look for new ways how to overcome it, particularly through the use of financial levers and instruments. The framework development of climate finances for regional and local levels will allow using country and regions finances more efficiently for fight against climate warming that is the main function of climate finances in the current environment.
Keywords: climate finances; structure of climate finances; challenges of climate finances functioning at regional and local levels; the Kyoto protocol, the Paris Agreement; European Union; special economic zones